2010
DOI: 10.1021/ja910602h
|View full text |Cite
|
Sign up to set email alerts
|

Solving the α-Conotoxin Folding Problem: Efficient Selenium-Directed On-Resin Generation of More Potent and Stable Nicotinic Acetylcholine Receptor Antagonists

Abstract: Alpha-conotoxins are tightly folded miniproteins that antagonize nicotinic acetylcholine receptors (nAChR) with high specificity for diverse subtypes. Here we report the use of selenocysteine in a supported phase method to direct native folding and produce alpha-conotoxins efficiently with improved biophysical properties. By replacing complementary cysteine pairs with selenocysteine pairs on an amphiphilic resin, we were able to chemically direct all five structural subclasses of alpha-conotoxins exclusively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
161
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(170 citation statements)
references
References 43 publications
7
161
0
2
Order By: Relevance
“…36 Meanwhile, researchers have investigated several toxins such as apamin and conotoxin for modification via partial or full replacement of disulfide bonds by diseleno bonds. 23,[39][40][41] The produced analogs were more stable than their native counterparts and structural analysis showed that the slightly larger atomic radius of selenium had no significant impact on the overall structure. 23 It was reported that disulfide bonds occurred in nearly 30% of proteins, 42 and many such peptides and proteins had important physiological functions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…36 Meanwhile, researchers have investigated several toxins such as apamin and conotoxin for modification via partial or full replacement of disulfide bonds by diseleno bonds. 23,[39][40][41] The produced analogs were more stable than their native counterparts and structural analysis showed that the slightly larger atomic radius of selenium had no significant impact on the overall structure. 23 It was reported that disulfide bonds occurred in nearly 30% of proteins, 42 and many such peptides and proteins had important physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…23,[39][40][41] The produced analogs were more stable than their native counterparts and structural analysis showed that the slightly larger atomic radius of selenium had no significant impact on the overall structure. 23 It was reported that disulfide bonds occurred in nearly 30% of proteins, 42 and many such peptides and proteins had important physiological functions. As a tumor-targeting moiety, a variety of disulfide-constrained peptides exist, especially those screened by phage display, such as CSNRDARRC peptide for bladder cancer, 43 CMGNKRSAKRPC for rhabadominosarcoma, 44 and CASPSGALRSC for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we reasoned that the relative stability of SeS-linked intermediates might play a role in the suggested biosynthetic pathway outlined in Scheme 1. Notably, the higher stability of selenenylsulfide bonds as compared to disulfides has been exploited for solving peptide-folding problems and in protein engineering; [54,55] in addition to the favorable formation of SeS over S 2 , [56] the former possesses a lower redox potential (typically 70 mV lower than the corresponding disulfides). [19] Glutathionyl-sugar conjugates 4 and 5, and glycoprotein SBL-C156-SSe-Glc 8 c were incubated in rat plasma.…”
mentioning
confidence: 99%